The Application of Permanent Magnet Motor on Electric Submersible Pump in X Well - Andreas Setiabudi; Muhammad Taufiq Fathaddin; Suryo Prakoso (Penerbitan Universitas Trisakti, 2020)
In thisresearch the application of permanent magnet motor and asynchronous motor in X Well was evaluated. The permanent magnet motor and asynchronous motor used in this research are PM51 – NFO 150 FLT @50hz and AM51 – NFO 150 FLT @50hz, respectively. Several parameters are compared such energy losses, energy consumption, motor heating, and production rate. Based on the data analysis, there are some advantages by using permanent magnet motor which can help to improve efficiency and consume less energy, therefore can give more profit within the same period of production. These advantages consist of durability for motor, consume less electricity energy to maintain the operation of ESP string, give bigger production rate, and longer expected life time than an asynchronous motor. The implementation of permanent magnet motor is recommended in oil well that has high fluctuation in production flow rate, since the setting flow rate of the motor is adjustable. This advantage can be useful to give longer lifetime and hence to reduce the pump replacement program